(untitled) (Innovative professional education, 2022)
The priority objective of higher education institutions lies in preparing futurespecialists who should be able to restore different spheres of life and reform the branches ofUkraine’s economy, given the consequences of Russia’s military aggression. Importantly, suchobjectives should be followed when updating the educational components of degreeprogrammes. This process depends on how effectively the latest achievements of science andeducational practices of the leading Ukrainian and foreign higher education institutions havebeen incorporated into the content of educational components.